Multi-objective dynamic distribution feeder reconfiguration in automated distribution systems. (15th March 2018) - Azizivahed, Ali; Narimani, Hossein; Fathi, Mehdi; Naderi, Ehsan; Safarpour, Hamid Reza; Narimani, Mohammad Rasoul
Abstract: Distribution feeder reconfiguration is an important operation problem in distribution system which has been used to improve the efficiency of distribution systems by obtaining the best combination of on/off status of the switches. It is a mixed integer non-linear program problem and hence hard to solve which necessitate employing proper optimization algorithms to converge to global optima or find near global optima. Smart grid implementation has made loads and electricity prices more volatile and as a result makes operational power system problems to be much more time dependent and more complicated rather than before. To cope with these time dependencies, it is crucial to extend the problems on different time intervals. To this end the dynamic distribution feeder reconfiguration, extension of the problem over multiple time intervals, with various objective functions including operation cost, power loss and energy not supplied is developed and investigated in this study. Time varying electricity prices and different load levels juxtapose with the effect of distributed generations are taken into account in order to generalize the proposed approach. Inherent complexities of distribution feeder reconfiguration problem have made proposing solution techniques an ongoing research topic. A new optimization algorithm is proposed to solve the proposed problem. Highlights: Expanding the distribution feeder reconfiguration problem on multiple time intervals. Considering the volatile electricity prices and loads in the problem. Taking reliability index, energy not supplied, into account. Implement the proposed method on a relatively large distribution system. Presenting new algorithm based on improved particle swarm optimization and improved grey wolf optimizer algorithms.